THE CORRELATION BETWEEN TEENAGE DAUGHTERS' ATTITUDES AGAINST EARLY MARRIAGE AND KNOWLEDGE LEVELS AT SMPN 2 INDRAMAYU IN 2023 - Dwi Anggi; Mira Mira Aryanti; Mayang Chyntaka (Jurnal Smart Kebidanan, 2024)
Background: An early marriage is one that happens when a person is less than 18 and is prohibited by law from marrying at this age. One of the factors causing early marriage is the lack of knowledge and attitudes of young women. Based on data from the Indramayu Religious Court in 2022, there were 572 incoming marriage dispensation cases. The highest marriage dispensation case in Indramayu Regency in 2022 occurred in Indramayu District with 28 cases. Objectives: To determine the relationship between the level of knowledge and attitudes of girls towards early marriage at Two State Junior High Schools Indramayu in 2023. Methods: This study used a quantitative method with a Cross Sectional approach. The population was 275 female students. The sample amounted to 130 respondents with Stratified Random Sampling technique. Instrument used a questionnaire. Data analysis using univariate and bivariate. Results: This study shows that there is a relationship between the level of knowledge and attitudes of adolescent girls towards early marriage at Two State Junior High Schools with a p-value = 0.002. Conclusion: There is a significant relationship between the level of knowledge and attitudes of adolescent girls towards early marriage at Two State Junior High Schools Indramayu.